Analysis of Teacher Learning Strategies to Improve Critical Thinking Skills of Elementary School Students - Kadek HengkI Primayana; Ni Komang Widya Sari Ratnadi; Kadek Yurin Harmelia; Putu Evita Ocean Ungga Putri; Desak Made Ari Sukma Dewi; Kadek Diani Arta Budi (Indonesian Journal Publisher, 2026)
This study aims to analyze teacher learning strategies in developing critical thinking skills in elementary school students through literature study methods. The low critical thinking skills of students in Indonesia are evident from the results of the Programme for International Student Assessment (PISA), which shows that students' abilities in analyzing information and solving problems are still in the low category. This condition is influenced by learning that is still teacher-centered and does not actively involve students. The results of the study indicate that expository, inquiry, problem-based learning, cooperative, contextual, affective, and Project Based Learning (PjBL) strategies can help students think logically, analyze problems, and solve problems independently. The inquiry strategy is considered most relevant to the Independent Curriculum because it places students at the center of learning through independent questioning, observing, discovering, and drawing conclusions. This strategy can train students' critical thinking skills more actively, systematically, and in-depth, thus becoming a solution to improve the quality of learning and student abilities, as reflected in the PISA results.